1,2-annulated adamantane heterocyclic derivatives as anti-influenza Α virus agents - Pardali, Vasiliki (Array, 2019)
In this report we review our results on the development of 1,2-annulated adamantane heterocyclic derivatives and we discuss the structure-activity relationships obtained from their biological evaluation against influenza A virus. We have designed and synthesized numerous potent 1,2-annulated adamantane analogues of amantadine and rimantadine against influenza A targeting M2 protein the last 20 years. For their synthesis we utilized the key intermediates 2-(2-oxoadamantan-1-yl)acetic acid and 3-(2-oxoadamantan-1-yl)propanoic acid, which were obtained by a simple, fast and efficient synthetic protocol. The latter involved the treatment of protoadamantanone with different electrophiles and a carbon-skeleton rearrangement. These ketoesters offered a new pathway to the synthesis of 1,2-disubstituted adamantanes, which constitute starting materials for many molecules with pharmacological potential, such as the 1,2-annulated adamantane heterocyclic derivatives. To obtain additional insight for their binding to M2 protein three structurally similar 1,2-annulated adamantane piperidines, differing in nitrogen position, were studied using molecular dynamics (MD) simulations in palmitoyl-oleoyl-phosphatidyl-choline (POPC) hydrated bilayers.